OP0167 Evidence That Both the Disease Course & Structural Outcomes in RA Have Become Less Severe over Time. A 25-Year Longitudinal Data Analysis Based on Two Consecutive UK Inception Cohorts. (10th June 2014) - Nikiphorou, E.; Norton, S.; Carpenter, L.; Dixey, J.; Kiely, P.; Walsh, D.; Young, A.
Abstract : Background: Evidence suggests that disease expression and course in RA has become less severe. It is unclear whether this is due to changes in disease phenotype/expression or reflects earlier more effective therapy. Objectives: To test the hypothesis that the course of RA & structural outcomes have become less severe in recent years. Methods: A total of 2701 DMARD-naïve patients were recruited over 25yrs in two UK RA inception cohorts with a single continuous mode of data collection:Early RA Study (9 centres, 1986-1998) & Early RA Network (23 centres, 2002-2012). Standardized clin/lab & x-ray measures were performed at baseline prior to DMARDs & yearly, along with comorbidities & in-patient hospital episodes including orthopaedic surgery (OS). Clinical databases were supplemented & validated with UK sources: National Joint Registry, Hospital Episode Statistics & National Death Register. Therapies included DMARDs, steroids & biologics based on standard UK practices and published guidelines. Results: Of 2701 early RA patients, 67% were female, mean age 56yrs (±14) & 62% rheumatoid factor positive (RF+ve), median follow-up 9 yrs (IQR 13). Over 25yrs of study, a shift towards more intensive therapy was seen: from monotherapy (1st choice DMARD: sulphasalazine in the 1st decade, methotrexate in the 2nd) to dual combinations, triple therapy & biologics. Graphics will dispay these trends. Over the recruitment periods, there was no significant change in gender (p=0.648), RF+ve (p=0.775), or erosions at baseline (p=0.695). Age at disease onset increased by 0.22 years/year (p=0.001), indicating a later disease-onset over time despite times from symptom onset to specialist diagnosis changing little (median 6 months). In models controlling for centre, age & gender, baseline clin/lab variables that significantly decreased with every year included:DAS (by 0.03 unit, p<0.001); tender & swollen joint counts [SJC](p<0.001);ESR by 0.8 units/year (p<0.001). Haemoglobin (HB) increased by 0.003unit/year (p<0.001). For all clin/lab variables, apart from SJC, graphs will show an observed linear trend over time. Excluding patients who used steroids prior to baseline (n=127) from analysis made no difference to the observed trends. 1602 OS were undertaken by 770 patients (29%): 585 major (mainly hip/knee replacements), 392 intermediate (mainly hand/foot procedures), and the rest were mainly minor (soft-tissue procedures). There was a significant decline in 10-year cumulative incidence of intermediate OS (p<0.001) paralleled by progressively earlier & more intensive therapy, but not in major/minor OS. Conclusions: Less severe measures of disease at presentation of RA to secondary care prior to DMARDs in recent years were seen, not explained by prior steroid use in primary care. The later-onset of disease with each progressive year may point towards an underlying demographic trend. In contrast, pathognomonic features of RA, baseline erosions & RF have not changed over time. There were significant declines in the rates of intermediate OS for RA over time, in parallel with more intensive treatments. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4972